Asymmetric autocatalysis induced by meteoritic amino acids with hydrogen isotope chirality - Kawasaki, Tsuneomi (Royal Society of Chemistry, 2009)

(untitled)
Achiral meteoritic amino acids, glycine and α-methylalanine, with hydrogen isotope (D/H) chirality, acted as the source of chirality in asymmetric autocatalysis with amplification of ee to afford highly enantioenriched 5-pyrimidyl alkanols.